FRI0306 Long term drug-free remission is feasible in severe behcet's disease after cessation of successful anti-tnf treatment: a single center, retrospective longitudinal outcome study. (15th June 2017) - Sfikakis, PP; Arida, A; Panopoulos, S; Fragiadaki, K; Pentazos, G; Laskari, A; Tektonidou, M; Markomichelakis, N
Abstract : Background: The efficacy of anti-TNF treatment for patients with severe forms of Behcet's disease (BD) is well established (ref), but long term data on the outcome after cessation of such treatment are lacking. Objectives: To examine whether sustained long term remission of severe BD is feasible after cessation of successful anti-TNF treatment. Methods: This retrospective longitudinal outcome study was conducted in December 2016 and included all patients with severe BD refractory to conventional immunosuppressive therapy who were considered complete responders to continuous anti-TNF treatment in our center, the first being treated in 2000. Study's endpoint was the proportion of patients achieving sustained complete remission of BD for at least 3 years after cessation of the anti-TNF agent. Results: A total of 28 patients in whom infliximab and/or adalimumab treatment was given, always combined with azathioprine unless not tolerated (n=2), and discontinued anytime before December 2013 were eligible for analysis. Following cessation of successful anti-TNF treatment (median duration of 2 years) 13/28 patients achieved the study's end-point. The main reason for anti-TNF administration was sight-threatening ocular disease (n=12) or intestinal disease (n=1). The remaining 15 patients relapsed within 1.5 year (main reason for anti-TNF: ocular disease, n=9; neuro-BD, n=2; severe mucocutaneous disease, n=3; intestinal disease, n=1; median treatment duration of 24 months); 12/15 were successfully re-treated with anti-TNF. So far, 3 of them (ocular disease, n=2; neuro-BD, n=1) have achieved the study's end-point (median re-treatment duration of 2 years). Overall, our 16 patients who achieved the study's end-point (57%) are in complete disease remission ranging from 3 to 12 years (5.7 years, median). Nine patients with severe ocular disease are currently any drug-free (32%), whereas the 7 remaining patients are on low doses of conventional immunosuppressive therapy (25%). Notably, those patients on drug-free remission had shorter median disease duration at initiation of anti-TNF treatment, compared to the remaining patients (1 versus 3 years, respectively). Conclusions: Sustained drug-free remission for many years after cessation of successful anti-TNF treatment is feasible in some patients with severe BD. Since anti-TNF-induced "cure" can never be differentiated from a spontaneous remission by natural history, further studies should examine whether early anti-TNF treatment must be intended for every patient with severe BD. References: Hatemi G, et al. EULAR recommendations for the management of Behçet disease. Ann Rheum Dis. 2008 Dec;67(12):1656–62. Disclosure of Interest: None declared